Impact of Multicultural Based Education Learning In the Process of Social Integration at SMA Al Azhar Mandiri Palu - Wisdayanti, Wisdayanti; Hasan, Hasan; Nadjamuddin, Lukman (Journal of Education Method and Learning Strategy, 2024)
Multicultural learning education is basically an educational program for the nation so that a multicultural community can participate in realizing the ideal life of democracy for the Nation. Formulation problem on study This is How learning education based on multiculturalism at Al Azhar High School Independent Palu, How impact learning education based multiculturalism has on students at Al Azhar High School Independent Hammer. Objective on study This Know the impact of learning education based on multicultural to students of Chinese ethnicity at Al Azhar High School Independent Hammer. Method study This is a qualitative method namely methods focused research attention on problems or natural phenomena actual at the moment study carried out And served in the form of a verbal narrative that describes facts about the problem being investigated How exists accompanied by rational interpretation And accurate . Results from study This Impact from learning based multicultural at Al Azhar High School Independent Hammer that is teach attitude value differences, attitudes deliberate, defend state, change mental attitude, knowledge citizenship, knowing rights and obligations inhabitant good country, guidelines Act in community, basics life nationality And matter the impact on students at Al Azhar High School Independent Hammer.